Targeting epidermal growth factor receptor pathway with irreversible tyrosine kinase inhibitor - Sagir, Fatma; Demiroğlu-Zergeroğlu, Asuman (Walter De Gruyter Gmbh, 2019)
Background: Malignant mesothelioma (MM) is an endemic disease around central Anatolia region in Turkey, where people are exposed to erionite- and asbestos-contaminated soil. Aberrant EGFR signalling has implicated in several cancers including MMs. Tyrosine kinase inhibitors are new treatment options harbouring deregulated signalling network components. In this study, we aimed to investigate anti-proliferative effect of CL-387,785 in MM cells. Materials and methods: Alteration of cell proliferation was evaluated with using MTS assay. Profile of EGFR, ERK, AKT, JNK and p38 proteins and ELK-1, JUN, STAT1, STAT3 and STAT5 genes were analysed by western blot and RT-PCR, respectively. Results: Viability of MM cells was inhibited in dose- and time-dependent manner. CL-387,785 affected MM cells earlier and at higher extent compared to the meso-thelial cells. CL-387,785 treatments suppressed EGF-induced phosphorylation of EGFR, ERK, AKT, STAT3 and STAT5 but not SAPK/JNK and p38 in SPC212 cells. RT-PCR analysis showed that expression of p21 increased, while Cyclin D and c-jun expressions decreased in SPC212 cells. However, ELK-1, STAT3 and STAT5, expressions did not change. Conclusion: Our results propose that CL-387,785 could be an efficacious agent in the treatment of MMs with uncontrolled EGFR signalling.
Keywords: Malignant mesothelioma; CL-387,785; EGFR; MAPK; AKT; STATs